Evaluation of the Success of TPP Information System Implementation Using the Hot-Fit Method - I Putu Eka Widyantara; I Made Gede Sunarya (Eduvest - Journal of Universal Studies, 2025)
The implementation of e-government systems often faces challenges in terms of adoption and sustainability, including employee incentive systems in the public sector. This study aims to evaluate the success of the implementation of a web-based and mobile Employee Income Supplement Information System (TPP) in the Karangasem Regency Government using the Human, Organization, Technology Fit (HOT-Fit) model approach. The evaluation was conducted by investigating the alignment between human factors (user satisfaction and usage), organizational factors (support and structure), and technological factors (system, information, and service quality), and their impact on the system's net benefits. Data were collected through a questionnaire survey of system users and analyzed using descriptive statistical techniques and Structural Equation Modeling (SEM) with SmartPLS software. The results showed that organizational and human factors significantly influenced the perception of system benefits, while technological aspects needed improvement, especially in terms of reliability and ease of use. This study identified an adoption gap caused by a lack of training, management support, and feature optimization. Theoretically, this study enriches the application of the HOT-Fit model in the context of government-to-employee (G2E) systems in Indonesia. Practically, these findings provide recommendations for local governments to strengthen organizational support, increase user capacity, and refine technical design to ensure the TPP system can achieve its goals in supporting fair and transparent performance assessment.